STRATEGIES OF SOCIAL ADAPTATION: LIFE HISTORIES OF THE THIRD GENERATION OF KOREANS IN KAZAKHSTAN - Yem, Н.; Kim, В. (Journal of Oriental Studies, 2024)
In Kazakhstan, the local ethnic Korean population is identified as an ethnic group that assimilates well within the country. Considering this, the authors of this article posit the following questions: What adaptation strategies and life values do the third generation of ethnic Koreans adhere to? What adaptive behaviors may be anticipated from the Korean ethnic group in the future? This paper analyses major integration trends of the third generation of Korean diaspora in Kazakhstan. Three strategies for adaptation (integration) are proposed in the context of post-Soviet independent Kazakhstan: education and professionalism; ethnic leadership; and transnational ties with South Korea. The authors test and analyze hypotheses regarding the influence of role models on the integration process into Kazakhstani society. This is achieved through content analysis of materials derived from journalistic articles alongside interviews with third and fourth generation ethnic Koreans. Analysis is conducted on materials gathered from the urban population of Koreans in Kazakhstan. The concept of the “ethnic enclave” was corroborated by the evidence of ethnic population concentration with high social and economic activity outside of geographically delineated borders. The concept of strong upward assimilation was supported by the life histories of third and fourth generation of ethnic Koreans in Kazakhstan. Overall, this article contributes significantly to the academic understanding of ethnic adaptation, integration, and assimilation in the context of post-Soviet Kazakhstan and the broader migration process. Keywords: ethnic Koreans, Kazakhstan, assimilation, integration, adaptation